Methodical rationale Programs Physical Rehabilitation arterial hypertension in undergraduate courses First medical university - Ivanko, O. G.; Mikhalyuk, E. L.; Pidkova, V. J. (Zaporozhye Medical Journal, 2013)
The article presents the organization questions and introduction methods of physical rehabilitation of arterial hypertension among young people. The rates of arterial pressure and body weight index are estimated as predictors of the students of the medical university including in physical rehabilitation programs.